QUALITY AND PRODUCTIVITY OF SORTS OF VEGETABLE MARROW ARE AT DIFFERENT TERMS OF SOWING IN THE WESTERN FOREST-STEPPE CONDITIONS - Гойсюк, Л. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
A study of biochemical composition of vegetable marrow and ground of his productivity is at the different terms of sowing of seed in the conditions of Forest-steppe Western. A laboratory method was used in researches – for determination of physical properties and agrochemical description of soil, and also for establishment of biochemical indexes of quality of vegetable marrow; field method – for determination of complex action of factors that was investigated in sowing of vegetable marrow in accordance with the hydrothermal terms of region. Influence of terms of sowing of vegetable marrow is educed on duration of vegetation period of plants. It is set that at sowing of seed of modern sorts of vegetable marrow in the third ten-day period of April the general productivity rose at a sort Chaclun on 28,1 т/ha comparatively with control, at a sort Haydamaka on 23,9 т/ha and at the sort of Zolotinka - on 27,7 т/ha. The commodity productivity of culture is investigational. Quality of vegetable products and importance of determination of this index are analysed in the modern terms of ménage. Results of the study were developed to the level of practical recommendations on perfection of technology of growing of vegetable marrow in the conditions of Foreststeppe Western. The offered terms of sowing of vegetable marrow assisted providing of the high productivity and high biochemical indexes of quality of marrow.